The performance of New Zealand initial public offerings (IPOs): 1995-2000 / Arizza Sapuan - Sapuan, Arizza (2004)
This study will focus on the long-term performance of initial public offerings in New Zealand for five years or 60 periods and three years of 36 periods from 1995 to 2004. This paper will analyze on 40 of IPOs companies that listed in 60 periods and 19 of IPOs companies that listed in 36 periods of New Zealand Stock Exchange (NZSE). NZSE 40 was used as a benchmark in evaluating share price performance. The objective of this study is to determine the long term performance of IPOs. This is in order to find out whether the New Zealand IPOs are under perform or over perform the market for the long run. Abnormal Return and Buy-and-hold Abnormal Return has been used to determine the long run performance of IPOs. Also used t-statistics skewness adjusted to see the significant of the IPOs. The result show that the performance of returns on all IPOs companies has no significant to the returns on the market for each period either 60 periods or 36 periods. So, I conclude that all IPOs companies do not under perform the market and it's comparable to the market as a benchmark.